Identification of the Potential Key Circular RNAs in Elderly Patients With Postoperative Cognitive Dysfunction - Gao, Rui; Chen, Chan; Zhao, Qi; Li, Ming; Wang, Qiao; Zhou, Lu; Chen, Erya; Chen, Hai; Zhang, Yue; Cai, Xingwei; Liu, Changliang; Cheng, Xu; et al. (Frontiers in Aging Neuroscience, 2020)
Background: Postoperative cognitive dysfunction (POCD) is one of the severe complications inducing low life quality and high mortality after surgery, especially in elderly patients. However, the underlying molecular mechanism of POCD remains largely unknown and the ideal biomarker for clinical diagnosis and prognosis is lacking. Circular RNAs (circRNAs), as a unique class of noncoding RNAs (ncRNAs), was characterized by its stably and conservativeness serving as novel biomarkers in various disease. Nevertheless, the role of circRNAs in the development of POCD remains elusive. Methods: To investigate the differentially expressed circRNAs in POCD patients and its potential role in the pathogenesis of POCD, we performed circRNA microarray to screen the differentially expressed circRNAs in 6 serum samples of POCD patients and non-POCD patients. Subsequently, quantitative real-time polymerase chain reaction analysis (qRT-PCR) to confirm the microarray data with 20 patients’ serum samples. Cytoscape software was used to construct the circRNA-miRNA-mRNA network for circRNAs with different expression levels as well as the target genes. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis showed the biological functions of differentially expressed circRNAs target genes. Results：In total, we have analyzed 10198 circRNAs through the microarray. Compared with the non-POCD patient group, there were 210 differentially expressed circRNAs with 133 ungraduated and 77 downgraduated in POCD group (≥ 2-fold differential expression, P ≤0.05). qRT-PCR confirmed 7 circRNAs with different expressed levels and the results were consistent with the microarray findings. The GO analysis showed that the differentially expressed circRNAs were associated with the regulation of developmental process, cell to cell adhesion and nervous system development. The KEGG analysis showed that the target genes of circRNAs were enriched in MAPK signaling pathway and RAS signaling pathway. According to the targetscan7.1 and mirdbV5 databases, the circRNA-miRNA-mRNA network were constructed and these results provided a vital landscape of circRNAs expression profile in POCD. Conclusions: Our study provides an important perspective for differential expression of circRNAs in POCD patients. Further studies need to be performed to explore their potential therapeutic roles in the development of POCD.